What makes an elite shooter and archer? The critical role of interoceptive attention - Li, P.; Lu, Q.; Wu, Q.; Liu, X.; Wu, Y. (Frontiers in Psychology, 2021)
It is well-acknowledged that attention is important for expert performance in sports. However, the role of interoceptive attention, i.e., the attentional mechanism of awareness and conscious focus of bodily somatic and visceral signals, in self-paced and far-aiming sports remains to be explored. This study aims to investigate the relationship of expertise level and interoceptive attention ability in shooting and archery, and to examine if interoceptive attention can be improved by mindfulness training in elite athletes of shooting and archery. We tested the performance differences of 41 elite athletes from the Chinese national team of shooting and archery and 43 non-elite athletes from a provincial team in breath detection task (BDT) and dot flash detection task (DDT), which were designed to measure interoceptive and exteroceptive attention (i.e., attention toward information input of primary sensory), respectively. Furthermore, we applied mindfulness training to the 41 elite athletes for 5-8 weeks and remeasured their performances of BDT and DDT. Results showed that elite athletes outperformed non-elite athletes in BDT (but not in DDT) both in accuracy (DiffBDT = 11.50%, p = 0.004) and in discrimination sensitivity (d', DiffBDT = 1.159, p = 0.002). Difference in accuracy and d' reached significant level only in BDT (accuracy: DiffBDT = -8.50%, p = 0.001; d': DiffBDT = -0.822, p = 0.003) before and after mindfulness training. These results indicate that elite athletes of shooting and archery (i.e., relative to non-elite athletes) can better perceive the somatic and visceral responses or changes and discriminate these signals from noises. Moreover, interoceptive attention can be improved by mindfulness training. These results have important implications for the selection and training of athletes of shooting and archery.